18F-fluoro-deoxy-glucose positron emission tomography combined with computed tomography can reliably rule-out infection and cancer in patients with anti-neutrophil cytoplasmic antibody-associated vasculitis suspected of disease relapse. Issue 30 (July 2017) - Frary, Evan C.; Hess, Søren; Gerke, Oke; Laustrup, Helle
Abstract : Abstract: Anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is a group of autoimmune diseases characterized by systemic inflammation in small- to medium-sized blood vessels. Although immunosuppressive therapy has greatly improved the prognosis for these patients, there are still significant comorbidities, such as cancer and infection, associated with AAV. These comorbidities are often indistinguishable from an underlying AAV disease relapse, and create a clinical conundrum, as these conditions are normally contraindications for immunosuppressive treatment. Thus, it is important to be able to rule out these comorbidities before initiation of immunosuppressive treatment. We examined 18 F-fluoro-deoxy-glucose positron emission tomography combined with computed tomography (FDG-PET/CT)'s value in ruling out cancer or infection in patients with AAV. Data were obtained retrospectively for a clinically based cohort of AAV patients who underwent FDG-PET/CT during 2009 to 2014 owing to a suspicion of cancer, infection, or both cancer and infection indistinguishable from disease relapse. FDG-PET/CT conclusions were compared to the final diagnoses after follow-up analysis (mean 43 months). A total of 19 patients were included who underwent a total of 26 scans. The results of FDG-PET/CT outcome compared to final diagnosis were: 9 true positives, 3 false positives, 13 true negatives, and 1 false negative. The diagnostic probabilities for FDG-PET/CT with respect to overall comorbidity (i.e., cancer or infection) were: sensitivity 90% ( 95% confidence interval [CI] 60%–98%), specificity 81% ( 95% CI 57%–93%), positive predictive value 75% (95% CI 47%–91%), negative predictive value 93% (95% CI 68%–99%), and accuracy 84% (95% CI 66%–94%). FDG-PET/CT had a high negative predictive value and ruled out the comorbidities correctly in all but one case of urinary tract infection, a well-known limitation. Our study showed FGD-PET/CT's promise as an effective tool for ruling out cancer or infection in patients with AAV albeit in a limited population.